Seroepidemiology of Human Hydatidosis Using AgB-ELISA Test in Arak, Central Iran. - Majid Asghari; Mehdi Mohebali; Eshrat Beigom Kia; Ali Farahnak; Mojgan Aryaeipour; Samieh Asadian; Mohammad Bagher Rokni (Tehran University of Medical Sciences, 2013)
On the continuation of sorting the puzzle of the situation of hydatid disease in Iran and considering that so far no survey was conducted in this context in Arak City, Markazi Province central Iran, the present study was conducted to determine the seroprevalence of human hydatidosis using AgB-ELISA test.Totally 578 serum samples randomly were collected from patients referred to hospitals and different health centers in the city and 3 nearby villages of Arak. All sera were examined by ELISA tests using AgB. Before sampling, a questionnaire was filled out for each case. Data were analyzed using Chi-square test and multivariate logistic regression for risk factors analysis. P